The design of an intelligent community portal for diabetes patient - Ab. Aziz, Azizi; Ahdon, Mohd Fadli; Mohd Hassin, Mohd Hafiz; Mat Hussin, M. Zaidil Adha; Siraj, Fadzilah; Sainin, Mohd Shamrie (2003)
Community services are among theimportant business aspect to strengthen theprofit and desired between industries andsocial responsibility alike.Therefore, there isa need for a competitive company to gaintrust and loyalty from their potentialconsumer.This project utilized knowledgebased technology to address the need of diabetes patient to improvise their quality of life.Based on the case study done at B BraunMedical (M) Industries Sdn. Bhd., the projectoffers an ample space of interaction betweenthe company and diabetic community viaWorld Wide Web.